WITTING OF PREVENTION OF SEXUAL HARASSMENT ACT - Snigdha Singh Dewal (Journal of Legal Studies & Research, 2021)
Women are stepping towards success; Sexual harassment at workplace is hindering accessibility in the milestone of education, Indian discernment and an act of forcibly depriving women’s to right and livelihood. Workplace harassment is a form of gender discrimination which violates woman’s fundamental right to equality and right to life provided under article 14, 15 and 21. To abrogate the discernment against women, the convention on the elimination of all forms of discrimination (CEDAW) describes any distinction, exclusion or restriction on the basis of sex, which lessens or diminishes the recognition or validity of women’s rights. In India; as stated under in the case Vishaka & Ors V State of Rajasthan, the Vishaka’s Guidelines are: It is the duty of an employer to protect the safety of their employees. Sexual harassment includes unpleasant sexually determined behavior as; Physical contact Demand or requests for sexual favours Sexual remarks Showing pornography Any other absurd verbal or non-verbal sexual demeanour The act considers that sexual harassment compromises the dignity of a woman and is a violation of her fundamental rights, as well as put out a partial yielding on a woman to carry on a profession or business in a free environment.